Community-based social healthcare practices in China for healthy aging: a social prescription perspective analysis - Menhas, Rashid; Yang, Lili; Danish Nisar, Rana (Frontiers in Public Health, 2023)
The global population is aging, and the number of people suffering from chronic diseases is increasing. In response to these trends, community-enhanced social healthcare practices are a novel paradigm of social prescribing that aims to improve both the community's and the individual's level of health by combining community involvement, organizational change, and individual-level practice. Objective: The study examined the state of community-based social healthcare practices using the lens of social prescription in China with an eye on promoting healthy aging there. Method: Thematic analysis, developed by Braun and Clarke (2006), was used in this investigation. A social prescription lens was used to conduct an open-ended theme study of China's community-based social healthcare practices for healthy aging. The research was conducted in Yiwu in Zhejiang Province, P. R. China. A sample of 24 "comprehensive evaluation team members (CETM)" was chosen using a purposive selection strategy. Results: In the context of the social prescription, we analyzed social healthcare practices for healthy aging at the community level. All the comprehensive evaluation team members described community social healthcare practices under the paradigm of social prescription. After analyzing the community social healthcare practices under the paradigm of social prescription, six main themes (E-Social Prescription, Nature-based Social Prescription, Healthy Living Social Prescription, Culture-based Social Prescription, Health Screening Social Prescription, and Health Education Social Prescription) emerged for healthy aging at the community level. Conclusion: Social prescribing links individuals to non-clinical services and activities, typically provided by the nonprofit and community sectors. Community-based social healthcare practices under social prescription can be an efficient and cost-effective way to assist patients with chronic diseases in managing their illnesses and enhancing their overall health and wellbeing.There will be significant challenges for China's healthcare system as the country's population ages. By 2050, China will have a population of 1.4 billion, with 400 million people aged 65 and over and another 150 million aged 80 and up. There is already a lot of pressure on the modern public